Relationship Marketing dan Jaringan Nilai di Koperasi Pertanian (Studi Kasus di Koperasi Pertanian Gerbang Emas di Desa Cibodas, Kecamatan Lembang, Kabupaten Bandung Barat, Jawa Barat) [Relationship Marketing and Value Networks in Agricultural Cooperatives: A Case Study of the Agricultural Cooperative Golden Gate in Cibodas Village, District Lembang, West Bandung Regency, West Java] - Rahmadian Melati; Agriani Hermita Sadeli (Universitas Pelita Harapan, 2017)
A cooperative has a purpose to prosper its members. One of the obstacles that often occurs is that the stakeholders of the cooperative’s business do not have functions in the function of the cooperative itself. This study aims to understand relationship marketing pattern and exchange of values at Koperasi Pertanian Gerbang Emas. The author collected data from in-depth interview with stakeholders and then categorize them based on six markets models in order to understand each stakeholder's role in relationship marketing. The value network is illustrated by holo mapping by seeing the exchange of values with stakeholders in goods, services, and revenues; knowledge; and intangible benefit. The results of this paper showed that Koperasi Pertanian Gerbang Emas does not have a complete role of its internal maket, Koperasi Pertanian Gerbang Emas members, which affects their relationship marketing pattern with other stakeholders. Exchange of values with stakeholders is in tangible products and even paid services that generate a cost or income. Exchange of knowledge values is in the form of workshops, cultivation of knowledge, technical use of technology, and also bookkeeping. Other than that, the exchange of intangible benefit values include trust and commitment. Improvement from internal markets of Koperasi Pertanian Gerbang Emas through a relationship marketing approach is needed to build trust and commitment of cooperative members.Bahasa Indonesia Abstrak: Sebuah koperasi mempunyai tujuan untuk mensejahterakan anggotanya. Kendala yang kerap terjadi di koperasi disebabkan oleh stakeholders dari bisnis koperasi yang tidak menjalankan fungsi dari koperasi. Tujuan penelitian ini ialah untuk mengetahui bagaimana pola relationship marketing, serta pertukaran nilai yang berlangsung di Koperasi Pertanian Gerbang Emas. Data diperoleh dengan wawancara mendalam kepada stakeholders yang bersangkutan dengan bisnis dari koperasi dan kemudian akan dikelompokan melalui six markets model yang berfungsi untuk mengetahui peran dari masing-masing stakeholders, dan jaringan nilai digambarkan melalui holo mapping dengan melihat pertukaran nilai dengan stakeholders dalam bentuk produk, jasa, dan pendapatan; pengetahuan; dan manfaat tidak berwujud. Hasil dari penelitian menunjukan bahwa Koperasi Pertanian Gerbang Emas belum memiliki peran yang seutuhnya terhadap internal market mereka, yaitu anggota koperasi, hal itu mempengaruhi pola relationship marketing Koperasi Pertanian Gerbang Emas dengan stakeholders lainnya. Pertukaran nilai yang terjadi dalam hubungan tersebut adalah pertukaran produk atau jasa yang menghasilkan biaya atau pendapatan. Pertukaran nilai dalam pengetahuan yang berupa pelatihan, wawasan budidaya, teknis penggunaan teknologi, serta wawasan mengenai pembukuan. Selain itu pertukaran nilai pada intangible benefit, meliputi rasa kepercayaan dan komitmen. Perbaikan dari internal market Koperasi Pertanian Gerbang Emas melalui pendekatan relationship marketing sangat dibutuhkan untuk menciptakan kepercayaan dan komitmen anggota Koperasi Pertanian Gerbang Emas.